Draft genome sequence of Neurospora crassa strain FGSC 73 - Baker, S. E.; Schackwitz, W.; Lipzen, A.; Martin, J.; Haridas, S.; LaButti, K.; Grigoriev, I. V.; Simmons, B. A.; McCluskey, Kevin (My University, 2015)
We report the elucidation of the complete genome of the Neurospora crassa (Shear and Dodge) strain FGSC 73, a mat-a, trp-3 mutant strain. The genome sequence around the idiotypic mating type locus represents the only publicly available sequence for a mat-a strain. 40.42 Megabases are assembled into 358 scaffolds carrying 11,978 gene models. © 2015 Baker et al.
Citation: Baker, S. E., Schackwitz, W., Lipzen, A., Martin, J., Haridas, S., LaButti, K., . . . McCluskey, K. (2016). Draft genome sequence of Neurospora crassa strain FGSC 73. Genome Announcements, 3(2). doi:10.1128/genomeA.00074-15
Citation: Baker, S., Schackwitz, W., Lipzen, A., . . . McCluskey, K. (2015). Draft Genome Sequence of Neurospora crassa Strain FGSC 73. Genome Announcements, 3(2), e00074-15. https://doi.org/10.1128/genomeA.00074-15